Massage Therapy In One Year Old Babies with Increased Appetie - Yulisetiyaningsih, Fera; Isro'aini, Any (Jurnal Kebidanan Midwiferia, 2024)
Massage often referred to as tactile stimulation, is a long-practiced art of health care and medicine. Baby massage can enhance the release of digestive hormones such as insulin and gastrin, leading to improved food absorption. This may result in the baby feeling hungry more frequently, potentially contributing to weight gain. Prolonged eating difficulties in children can lead to disrupted nutritional intake, including deficiencies in calories, protein, vitamins, minerals, electrolytes, and anemia. The study used a retrospective data analysis design with a chi-square test, involving a sample of 20 babies who received 12 massage sessions at Momby Kids Jombang. The total sampling method was employed. The findings revealed a significance value of 0.003, indicating a statistically significant relationship between baby massage and increased appetite. The study concluded that baby massage is indeed linked to an increase in appetite in babies.